Relevance of preclinical rodent pharmacokinetics in the selection of a companion antibiotic for combining with beta-lactamase inhibitor. (2nd July 2020) - Giri, Poonam; Delvadia, Prashant; Ladani, Meera K.; Prajapati, Namrata; Joshi, Vipul; Giri, Shyamkumar; Patel, Nirmal; Jain, Mukul R.; Srinivas, Nuggehally R.
Abstract: Recent approvals of beta-lactamase inhibitor (BLI) drug in combination with cephalosporins/penems have provided the right impetus for novel BLIs. One important research question, hitherto not addressed, is pertaining to the relevance of preclinical pharmacokinetics for pairing the antibiotic with existing/novel BLI. Two BLI combination drugs: (a) approved (i.e. ceftazidime/avibactam); (b) clinical development (i.e. cefepime/zidebactam) were explored to provide insights to address the research question. Individual intravenous dosing of ceftazidime, avibactam, cefepime and zidebactam was done at 1 mg/kg by intravenous route in Balb/c mice and Wistar rats. Serial blood samples were collected and analysed by LC–MS/MS method. Examination of the ratios of pharmacokinetic parameters (CL, V SS and T 1/2 ) for individual drugs in combinations (for instance, CL (ceftazidime)/CL (avibactam); CL (cefepime)/CL (zidebactam)) suggested that the pharmacokinetic data gathered in rats were generally within 0.5- to 2-fold; but mouse data revealed larger disparity for V SS (0.11- to 8.25-fold) or CL (0.49- to 4.03-fold). The observed ratio for CL/ V SS observed in rats agreed with corresponding human ratios for the pairwise comparison of the individual drugs in the combinations. Retrospectively, current pharmacokinetic findings suggest rat pharmacokinetic data may aid the combination of BLI with an appropriate antibiotic.